Le concept d'union économique dans la Constitution canadienne : de l'intégration commerciale à l'intégration des facteurs de production - Bernier, Ivan (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
The object of this paper is to assess the constitutional position as to economic integration within Canada. Following a short review of'the basic elements of economic integration, it proceeds to analyse the law and practice relating to the free circulation of goods, and the free movement of persons, services and capital in Canada. Since such questions are usually associated with the concept of common market, a brief comparison is made on these various points with the practice of the European Economic Community. As far as concerns the free circulation of goods, the study starts with the usual distinction between tariff and non-tariff barriers. If customs duties have long since disappeared between the provinces, the author finds that charges having an effect equivalent to customs duties are not totally precluded under Canadian constitutional law, and as a matter of fact are occasionally encountered in practice. The paper also shows that if non-tariff barriers to interprovincial trade are theoretically precluded under s. 91(2) of the B.N.A. Act, certain types of obstacles not only appear constitutionally acceptable, but also are largely used by governments in practice, such as preferential purchasing policies, subsidies, public enterprises, etc. In the end, when our constitutional rules pertaining to the free circulation of goods are compared with those in application within the European Economic Community, they appear less stringent, leaving greater room for intervention to the provinces. The situation, as far as concerns the free movement of persons, services and capital is quite different. As the study finds, there are no clearly articulated principles relating to these questions in the Canadian constitution. However, due to the existence of a common nationality and a common currency, the most serious difficulties in this respect have been avoided. From that point of view, Canada has benefited from a clear advantage over the European Economic Community. Yet, regarding the free movement of persons and services, the paper shows that whereas no progress appears to have been made on that score within the last decade in Canada, the E.E.C. is pushing forward with plans calling for the common recognition of diplomas, etc. And regarding the free movement of capital, it appears that if the E.E.C has not progressed much since the first years of the Treaty of Rome, Canada for its part appears at the moment to be heading for a period of greater restriction on the movement of capital within the country. In conclusion, the question is raised whether the material division of jurisdiction between the federal and provincial governments, as opposed to a functional division of jurisdiction as is to be found in the E.E.C, is not responsible for the centripetal kind of federalism that appears more and more in demand in Canada as far as concerns economic matters. Acting unilaterally on the basis of its exclusive powers, the federal government has adopted so-called common policies that appear to have met with a large measure of disapproval from the various provinces. But this is a different problem that requires a separate treatment.